2019
DOI: 10.1002/adsc.201900227
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient One‐Pot Enzymatic Synthesis of Cardiac Glycosides with Varied Sugar Chain Lengths

Abstract: An efficient one‐pot enzymatic synthesis of cardiac glycosides with varied sugar chain lengths (average yield >80%) was carried out through sequential glycosylation using a steroid glycosyltransferase UGT74AN3 from Catharanthus roseus and a cyclodextrin glycosyltransferase from Bacillus licheniformis. A series of cardiac glycosides were obtained and showed enhanced affinity and selectivity for inhibition of the α2 isoform of Na+/K+‐ATPase. These findings demonstrate the significant potential of the one‐pot bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 48 publications
(25 reference statements)
1
16
0
Order By: Relevance
“…Compared to PU-G , the glucoside with three sugar moieties ( PU-2G ) and the glucoside with four sugar moieties ( PU-3G ) were less potent, indicating that two sugar units are optimal for both the ALP activity and the expression of runx2. This is consistent with our previous results that the drug with an appropriate sugar chain length has the strongest activity . Recently, pharmacokinetic parameter analysis revealed that the PU- glycosylated compounds were absorbed more efficiently than the original compounds .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Compared to PU-G , the glucoside with three sugar moieties ( PU-2G ) and the glucoside with four sugar moieties ( PU-3G ) were less potent, indicating that two sugar units are optimal for both the ALP activity and the expression of runx2. This is consistent with our previous results that the drug with an appropriate sugar chain length has the strongest activity . Recently, pharmacokinetic parameter analysis revealed that the PU- glycosylated compounds were absorbed more efficiently than the original compounds .…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with our previous results that the drug with an appropriate sugar chain length has the strongest activity. 32 Recently, pharmacokinetic parameter analysis revealed that the PU-glycosylated compounds were absorbed more efficiently than the original compounds. 47 These results indicate that these high solubilities of transglycosylation products can be used as a substitute for PU.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…[5,6] Glycosylation modification can enhance the water solubility, [7] targeting [8] and reduce the toxic and side effects of drugs. [9] Both chemical method [10] and enzymatic method [11] can achieve glycosylation, but enzymatic glycosylation has the advantages of green and high efficiency, [12] and thus its application is increasingly widespread. This article intends to modify bufalin via the chemo-enzymatic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…But clinical application of bufalin is limited due to poor water solubility and large toxic side effects [5,6] . Glycosylation modification can enhance the water solubility, [7] targeting [8] and reduce the toxic and side effects of drugs [9] . Both chemical method [10] and enzymatic method [11] can achieve glycosylation, but enzymatic glycosylation has the advantages of green and high efficiency, [12] and thus its application is increasingly widespread.…”
Section: Introductionmentioning
confidence: 99%